Asia's lands and peoples : - Cressey, George Babcock (McGraw-Hill, 1944)
This is part of a series on the world it's people and the geography. The book is in good cond. lightly tanned and the hinge on the front board is slightly loose the paper is intact. the boards have marks of age and use but still a nice collectable copy.